Delay in diagnosis of Pulmonary Tuberculosis in Portugal - Filipe, Patrícia A. (2013)
Our main purpose is to achieve a better understanding of the several factors that are explicitly related with the time between the onset of the first symptoms and the diagnosis of Pulmonary Tuberculosis (“delay” in diagnosis) and its possible role on the level of the disease incidence. The length of such delay under scope is extremely important in Tuberculosis dissemination, since the baciliferous patient circulates freely, being a source of infection and constituting a danger to the health of susceptible people. The period 2000–2009 was studied and the official Tuberculosis Surveillance database was used. Survival Analysis methodologies were applied for the characterization of the delay in diagnosis of Pulmonary Tuberculosis in which the event of interest is the diagnosis of the disease. Some explanatory variables for the delay were also considered: region, age, sex and some risk factors for Tuberculosis (e.g., drugs consumption, HIV infection), among others. At this stage factors connected to the health services system that may explain the delay were not considered. The delay in diagnosis looks, in general, excessive and much variable for a satisfactory control, and presents some differences between the categories for sex, age groups, drugs consumption, new case/relapse and HIV status. Only between critical (high risk) and non critical geographical areas the delay in diagnosis seems identical. As a global conclusion this study indicates a possibly higher probability of (earlier) diagnosis when patients are male, young or HIV positive. This evidence suggests that the delay in diagnosis is reflecting some differences according to risk factors, which may be substantially improved by both customized services and patients’ awareness.